An experience with 53 patients of transanal endorectal pull-through for Hirschsprung’s disease - Buranakitjaroen, Veera; Mahatharadol, Varaporn (Chulalongkorn Medical Journal, 2023)
Background : Transanal endorectal pull-through (TEPT) has been widely used in the treatment of Hirschsprung’s disease (HD). We have been using this technique as described by Mondrag n and Ortega - Salgado in our hospital since January 2004. Objective : To evaluate the results of TEPT in the management of HD. Design : Retrospective study. Setting : Queen Sirikit National Institute of Child Health. Method : Fifty - three patients underwent TEPT for HD from January 2004 to March 2011. Patients’ hospital records were retrospectively analysed. The collected data included associated anomalies, age at diagnosis, enterocolitis before TEPT, weight at pull-through, site of transition zone, initial colostomy, primary TEPT without colostomy, age at pull-through, average length of resected bowel, operating time, blood loss, postoperative complications, daily bowel movements and continence. Follow-up period ranged from 2 weeks to 84 months. Results : The mean operating time was 210 minutes. Average length of resected bowel was 13 cm. Average blood loss during operation was 24 cc. Transition zone was noted at rectosigmoid region in 36 patients (68%). Age at operation under six months was documented in 36 patients. Seven patients had anastomotic stricture managed by anal dilatation and additional anoplasty in 1 case. Twenty-one patients suffered from attacks of enterocolitis postoperatively at least one time. Frequent bowel movements gradually improved with time. Normal bowel function was documented in 46 of 53 patients (87%). Conclusions : A one-stage pull-through for HD can be successfully performed using a transanal approach without intraperitoneal dissection. It takes less time, and has less bleeding, earlier recovery, less complication and no visible scar. Careful long-term follow up is required to assess daily bowel movements and continence.